Patient-Level Factors Associated With Referral Rates to Mental Health Services in a Network of Student-Run Free Clinics: A Pooled Cross-Sectional Study - Moothedan, Elijah; Katoju, Sri Varsha; Nguyen, Oliver T; Faldu, Aashi; Motwani, Kartik; Feller, David B (Journal of Student-Run Clinics, 2024)
Background: Student-run free clinics (SRFC) may offer needed mental health care to low income and uninsured populations who may have greater risk of mental illness. To date, there is limited literature assessing what patient-level factors are predictors of referrals to mental health services. Method: Medical record data came from a SRFC network on patients with depression, anxiety, and/or bipolar disorder (n=1,180). The dependent variable was whether patients received a mental health service referral, defined as an accepted internal referral to the study site’s mental health resources or external referral to a community mental health center. We conducted a binary logistic regression model to assess the relationship between various patient-level factors (age, primary language, insurance status, sex, race, ethnicity, and education status) and an accepted mental health referral. Results: Approximately 65.5% of patients received and accepted a mental health referral. Older patients had higher referral odds while males and high school diploma/vocational/associate degree holders had lower odds. There were no statistically significant differences in the odds of receiving a mental health referral by ethnicity, race, insurance status, or primary language. Conclusion: Elderly individuals were more likely to be accept referrals for mental health services, whereas male patients or those with a lower educational attainment were less likely to receive and accept such referrals. Future research should examine the role of patient attitudinal factors (e.g., perceived efficacy of mental health services, treatment preferences) and clinician-level factors on referral to mental health services. This article contains a correction, doi: 10.59586/jsrc.v10i1.417.g358.